Eksplorasi Persepsi dan Tantangan Mahasiswa Pendidikan Agama Islam Terhadap Ketergantungan Pornografi Pada Remaja - Achmad Jazuli; Sholihudin Al Ayubi (Jurnal Pendidikan Agama Islam Miazhar, 2024)
The many criminal incidents in the digital era such as sexual harassment and pornography addiction are challenges for Islamic Religious Education Students as the spearhead in education and application of religious and social knowledge. Therefore, there needs to be an effort to prevent and understand students regarding the perception and challenges of overcoming and preventing pornography addiction which can have fatal consequences. The formulation of the problem is 1) how is the perception of Islamic Religious Education Students of Al Azhar Institute in responding to pornography addiction among adolescents, 2) What are the challenges of Islamic Religious Education Students of Al Azhar Institute in preventing pornography addiction among adolescents, 3) What is the descriptive solution for preventive measures related to pornography addiction among adolescents? This type of research is qualitative with a survey approach. Data collection techniques are interviews and documentation. Data analysis techniques are the Miles and Huberman analysis model. The results of the study are First, the understanding of pornography as an intimate scene on social media, sexually stimulating images or videos, vulgar content without clothes or with body curves. Second, the spread of pornographic content on social media has a negative impact on the psychology and views of adolescents, violates privacy, and has the potential for abuse. Third, the impact of pornography addiction on adolescents such as emotional disorders, decreased achievement, anxiety, depression, and negative sexual behavior. The solution is to instill our love for God and strengthen spiritual relationships through worship, take an individual approach with heart and give advice interspersed with casual conversations, discuss a problem with a group of teenagers, without having to mention who is being talked about, limit the use of gadgets and schedule daily activities and gather with people who have the goal of stopping PMO.